Civil liability for infringement of the right to honor and consideration. Study/comparison - Assistant Professor Dr. Thamer Jassim Mohammed (The college of law and political science journal, 2025)
The human right to honor and consideration is considered one of the rights inherent to the personality and cannot be separated from it. This right has received the attention of international law and civil laws. Any infringement on this right requires civil liability, which requires an error represented by slander, defamation and insult, which causes harm to the victim, and results in the right of the injured party to compensation as the most important effect of civil liability. Compensation is for moral damage, as its location is the human conscience, which is the repository of his thoughts and feelings and the reason for his honor over all other creatures. This is because the human being’s ability to earn is linked to his stability. In fact, everything he has previously earned becomes worthless if his conscience is not stable. As such, and as a non-financial loss, it cannot be erased and removed by monetary compensation. However, the most that the legislator intended by stipulating it is to find an objective equivalent for this damage that is equal to it and bears the yoke of pain, sadness and grief for him, thus alleviating it.